Liljana Arsovska (ed.), Vidas. Cuentos de China contemporánea, México, El Colegio de México, 2013, 244 pp. - Martha Elena Venier (El Colegio de México, A.C., 2014)
Liljana Arsovska (ed.), Vidas. Cuentos de China contemporánea, México, El Colegio de México, 2013, 244 pp.